598 Patients' Knowledge and Compliance with Government Guidelines for COVID 19. (4th May 2021) - Eskander, J; Khallaf, A; Zaki, S; Elkawafi, M; Makar, R
Abstract: Background: Since the outbreak of COVID-19; social distancing and recognized effective precautions were recommended by various governments to fight the viral spread. Our aim was to assess the inpatient knowledge and compliance with the government guidelines during their hospital stay and at their discharge in two different NHS hospitals. Method: The study took place in two hospitals: Berrywood hospital, UK and Countess of Chester hospital, UK. We invited inpatients to answer an anonymized questionnaire which was designed to include the contemporary government guidelines. We excluded patients with cognitive impairment and those who were not expected to be discharged within days. Results: Out of 209 patients, 50% were male. Patients showed good awareness of the main symptoms of the virus (90%). However, A significant number of patients were not fully aware of the recommended precautions to minimize viral spread (28%) and the method of spread (43%). About 41% did not know the recommended safe distance. Conclusions: Despite being aware of the main symptoms of COVID-19, a significant number of patients lack essential information needed to minimize the spread of the virus in the society and hospital. We recommend providing patients with information leaflets and direct advice on admission and discharge.